Gestión de riesgos ergonómicos en los puestos de trabajo del personal que labora en el Gobierno Autónomo Descentralizado parroquial rural “San Lorenzo”, provincia Bolívar. - Núñez Peñaloza, Alejandra Mariela (2025)
This study aimed to manage ergonomic risk factors in the workstations of the staff at the Decentralized Autonomous Parish Government of “San Lorenzo,” located in Bolívar Province. The process involved identifying, assessing, and proposing preventive strategies. A mixed method approach was employed, combining quantitative and qualitative techniques with structured questionnaires, direct observations, and ergonomic assessment tools such as RULA and ROSA. The research followed a non-experimental, descriptive, bibliographic documentary, and field-based design. The findings revealed the presence of various risk factors, including poor posture, repetitive movements, and extended periods in static positions, which primarily affect the neck, shoulders, back, and wrists. Additionally, deficiencies in workplace furniture were identified, including uncomfortable seating and the lack of footrests. In conclusion, the study determined that employees are exposed to ergonomic conditions that may compromise their occupational health. As a result, a postural procedures manual was developed, aimed at improving working conditions and preventing musculoskeletal disorders.